Acute Kidney Injury Following Percutaneous Coronary Intervention for Acute Coronary Syndrome: Incidence, Aetiology, Risk Factors and Outcomes. (February 2022) - Carande, Elliott J; Brown, Karen; Jackson, David; Maskell, Nicholas; Kouzaris, Loukas; Greene, Giles; Mikhail, Ashraf; Obaid, Daniel R
We investigated the predictors, aetiology and long-term outcomes of acute kidney injury (AKI) following urgent percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS). Acute kidney injury occurred in 198 (7.2%) of 2917 patients: 14.1% of AKI cases were attributed to cardiogenic shock and 5.1% were classified as atheroembolic renal disease (AERD). Significant risk factors for AKI included age (odds ratio [OR] 1.05, 95% confidence limits [CI] 1.03-1.06), diabetes (OR 1.73, 95% CI 1.20-2.47), hypertension (OR 1.43, 95% CI 1.03-2.00), heart failure (OR 3.01, 95% CI 1.58-5.57), femoral access (OR 1.50, 95% CI 1.03-2.15), cardiogenic shock (OR 2.03, 95% CI 1.19-3.37) and ST-elevation myocardial infarction (STEMI) (OR 3.89, 95% CI 2.80-5.47). One-year mortality after AERD was 44.4% and renal replacement therapy (RRT) requirement 22.2% (compared with mortality 33.3% and RRT requirement 7.4%, respectively, in all other AKI patients). Mortality at 1 year was associated with AKI (OR 4.33, 95% CI 2.89-6.43), age (OR 1.08, 95% CI 1.06-1.09), heart failure (OR 1.92, 95% CI 1.05-3.44), femoral access (OR 2.05, 95% CI 1.41-2.95) and cardiogenic shock (OR 3.63, 95% CI 2.26-5.77). Acute kidney injury after urgent PCI is strongly associated with worse outcomes. Atheroembolic renal disease has a poor outcome and a high likelihood of long-term RRT requirement.